2010
DOI: 10.1093/brain/awq275
|View full text |Cite
|
Sign up to set email alerts
|

The decrease of β-synuclein in cortical brain areas defines a molecular subgroup of dementia with Lewy bodies

Abstract: Lewy body diseases include dementia with Lewy bodies and Parkinson's disease. Whereas dementia with Lewy bodies and Parkinson's disease can be distinguished as separate clinical entities, the pathological picture is very often identical. α-synuclein aggregation is a key event in the pathogenesis of Lewy body diseases and β-synuclein inhibits α-synuclein aggregation in vitro and in vivo. Recently, β-synuclein has been shown to interact directly with α-synuclein, regulating its functionality and preventing its o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 41 publications
2
51
0
Order By: Relevance
“…Previous studies of ours have shown that in FC the main transcript (SNCA140) is diminished in pure DLB and does not show important changes in common DLB [13]. Recently, we have also reported that brains with pure LBP from patients with relative short duration of DLB lack BS expression in cortical regions, especially in TC [20]. Part of our present data underline these results showing the drastic diminution of all SNCB transcripts in the cortex of G-pDLB.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Previous studies of ours have shown that in FC the main transcript (SNCA140) is diminished in pure DLB and does not show important changes in common DLB [13]. Recently, we have also reported that brains with pure LBP from patients with relative short duration of DLB lack BS expression in cortical regions, especially in TC [20]. Part of our present data underline these results showing the drastic diminution of all SNCB transcripts in the cortex of G-pDLB.…”
Section: Discussionsupporting
confidence: 84%
“…Since high-quality RNA cannot be taken for granted when dealing with PM brain samples [30], we assessed SNCB isoform, human neuron-specific enolase 2 (NSE), and synaptophysin (SYP) mRNA degradation rates in order to assure that they presented similar stabilities even at RIN values of about 6 as described before [20].…”
Section: Source Of Tissuesmentioning
confidence: 99%
See 2 more Smart Citations
“…So far it is known that equimolar β-Syn protein concentrations inhibit Aβ fibril formation in vitro [24]. Decreased β-Syn mRNA levels were found in AD patients compared to healthy controls [2,50,51]. Consequently, we have investigated the effects of wt β-Syn in a tg animal model of AD (APP SL animals) over a distinct time period.…”
Section: Discussionmentioning
confidence: 99%